2016
DOI: 10.3390/ijms17091528
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bioactivity, Volatile and Fatty Acid Profile in Supercritical Fluid Extracts of Mexican arnica

Abstract: Supercritical fluid extraction (SFE) is a sustainable technique used for the extraction of lipophilic metabolites such as pigments and fatty acids. Arnica plant is considered a potential candidate material with high antioxidant and antimicrobial activities. Therefore, in this study, a locally available Heterotheca inuloides, also known as Mexican arnica, was analyzed for the extraction of high-value compounds. Based on different pressure (P), temperature (T), and co-solvent (CoS), four treatments (T) were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…For instance, some of the drawbacks associated with these techniques include their long extraction time, high energy consumption, and waste generation. Besides, conventional techniques are limited in extraction specificity, then purification steps are required in order to isolate the bioactive metabolites of interest [ 49 , 50 ], whereas, SFE shows great extraction selectivity, short processing times, and a low degradability of the extracted product [ 51 , 52 , 53 ], without the use of non-food grade solvents [ 54 ]. SFE uses supercritical fluids, which above their critical point exhibit liquid-like characteristics such as solvent power, and negligible surface tension, etc.…”
Section: Extraction Methodologies For Bioactive Compoundsmentioning
confidence: 99%
“…For instance, some of the drawbacks associated with these techniques include their long extraction time, high energy consumption, and waste generation. Besides, conventional techniques are limited in extraction specificity, then purification steps are required in order to isolate the bioactive metabolites of interest [ 49 , 50 ], whereas, SFE shows great extraction selectivity, short processing times, and a low degradability of the extracted product [ 51 , 52 , 53 ], without the use of non-food grade solvents [ 54 ]. SFE uses supercritical fluids, which above their critical point exhibit liquid-like characteristics such as solvent power, and negligible surface tension, etc.…”
Section: Extraction Methodologies For Bioactive Compoundsmentioning
confidence: 99%
“…Fatty acids were determined through derivatization to fatty acid methyl esters (FAMEs) as previously described [ 24 , 60 , 62 ]. Briefly, samples were mixed with 400 μL of the internal standard (undecanoic acid 1000 mg/L in hexane/acetone 80:20 v/v) and 2 mL of methanol/sulfuric acid (93:7 v/v).…”
Section: Methodsmentioning
confidence: 99%
“…[ 10 ] Furthermore, a study showed that caryophyllene compounds not only have anti-cancer properties, but also act as antibiotics. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Each final fraction obtained was evaporated in a rotary evaporator and analyzed by gas chromatography-mass spectrometry (GC-MS) (Shimadzum, bnv, Japan). [ 5 6 ]…”
Section: Methodsmentioning
confidence: 99%